Analysis of Nursing Care for the Elderly with the Application of Progressive Muscle Relaxation Therapy to Reduce Blood Sugar Levels in Diabetes mellitus - jessika septia ningrum; Siska Mayang Sari; Rajunitrigo; Yumiati (Journal of Health Empowerment and Interprofessional Practice, 2026)
Background of study: The aging process accompanied by a decline in physiological and psychological functions makes the elderly more susceptible to impaired blood glucose control. Type II diabetes mellitus is one of the most common chronic diseases experienced by the elderly and is a major health problem because it can reduce the quality of life and increase the risk of various complications.Aims and scope of paper: This application aims to analyze nursing care for Mrs. R and Mrs. M and evaluate the application of progressive muscle relaxation therapy in lowering blood sugar levels in type II diabetes mellitus at the UPT PSTW Husnul Khotimah, Riau Province Social Service correctly, precisely and in accordance with professional nursing standards.Methods: The application method uses a case study with an evidence-based nursing approach totaling 2 subjects. This research instrument uses an observation sheet. The intervention time is 15 minutes in the time span from 10:00-11:00 WIB.Result: The results of random blood sugar levels (<200 mg/dl) for 3 days with an average value before therapy of 263 mg/dl and after therapy of 225 mg/dl.Conclusion: The conculusion of progressive muscle relaxation therapy have been proven to reduce blood sugar levels.